A prática do autocuidado após a revascularização do miocárdio - Lima, Francisca Elisangela Teixeira (2002)
The most important objective of post surgical orientation should be the practice ofthe selfcare by the people who have been submirted to the myocardium revascularization. The aim ofthis research is to investigate patienfs behaviour after the myocardium revascularization surgery, based on Orem's model (1995). It is a exploratory-descriptive study, with predominantly quantitative analysis, which was done in a cardiology clinic of a govemment hospital, in Fortaleza city, Ceará. The sample was composed by patients who: attended the doctor appointment from May to August in 2001; undergone a myocardium revascularization operation from July, 1999 to August, 2000; have been undergone an myocardium revascularization operation only once and agree on participating voluntarily in this research. Individualised interviews were applied at the nursing clinic before and after the medicai advice. The 52 patients interviewees, showed the following aspect: The majority were men (53,84%), from 65 years-old up (59,61%), retired (71,15%), married (63,46%), with family predispôsition for cardiovascular alterations (67,30%). The results related to selfcare practice were: 51 people (98,07%) attended regularly the doctor appointment and take medicine; 27 people (51,92%) showed IMC > 25 Kg/m2 (corporeal rate mass); 37 patients (71,15%) practise physical exercises at least three times a week; no one keeps smoking; 46 patients (88,46%) don't drink, but six patients still take alcoholic drink; 42 patients (80,76%) eat healthy food with fruits and vegetables; 63,46% reduced the use of salt; 40,38% reduced the ingestion of coffee and nine quit it completely; 76,92% say they have a calm temper mostly; 32 patients (61,53%) showed an arterial hypertension diagnosis, but 28,84% showed an arterial pressure equal or superior then 140 x 90 mmHg; 17,30% are diabetic with controlled glycohaemia levei. According to selfcare levei, 50,00% are very good; 32,69% are good and 17,30% are reasonably good, what shows that they follow the received orientations. Women, elderly patients, married patients and the ones who have family predispôsition for cardiovascular alterations practise selfcare better, mainly when the patient is retired. It is evident the necessity of adapted orientations for those who continue working. The conclusion is that patients that participated in this research, keep a satisfactory selfcare levei, supporting the importance of the orientation process in group, in a continuous way and with different approaches to provide to the patient who have been submitted to the myocardium revascularization conditions to do the selfcare practice.